Respuesta :

Answer:

The answer to your question is:

Step-by-step explanation:

12.-

                x² - 6x = 5

                x² - 6x + (3)² = 5 + (3)²

               x² - 6x + 9 = 5 + 9

               (x - 3)² = 14

13.-           x² - 6x = 12

               x² - 6x + (3)² = 12 + (3)²

               x² - 6x + 9 = 12 + 9

              (x - 3)² = 21

              x - 3 = ±√21

             x1 = √21 + 3                     x2 = -√21 + 3

               x1 = 7.58                           x2 = -1.58

14.-           2x² - 24x = - 20            Divide by 2

                x² - 12 x = -10

               x² - 12x + (6)² = - 10 + (6)²

               x² - 12x + 36 = - 10 + 36

              ( x - 6) ² = 26

               x - 6 = ±√26

x1 = √26 + 6                                 x2 = -√26 + 6

x1 = 11.1                                          x2 = 0.9